Fourier Analysis of Corneal Irregular Astigmatism After Small Incision Lenticule Extraction and Comparison to Femtosecond Laser-Assisted Laser In Situ Keratomileusis. Issue 12 (December 2019) - Sideroudi, Haris; Sekundo, Walter; Kozobolis, Vassilios; Messerschmidt-Roth, Anke; Lazaridis, Apostolos
Abstract : Purpose: Evaluation of spherical component (SC), regular astigmatism (RA), and irregular astigmatism (IA, ie, Asymmetry and Irregularities) 3 years after small incision lenticule extraction (SMILE) and comparison to femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK). Methods: Thirty-two eyes of 21 patients who underwent SMILE for myopia and astigmatism were compared with 32 eyes of 21 patients treated with FS-LASIK. Scheimpflug images were obtained preoperatively and 3 years postoperatively. Fourier analysis of keratometric-derived parameters (SC, RA, Asymmetry, and Irregularities) of the anterior, posterior, and total cornea were evaluated at 4 concentric rings (ring 1, 2 mm diameter; ring 2, 4 mm; ring 3, 6 mm; ring 4, 8 mm) and over the entire 8-mm zone. Results: After FS-LASIK, over the 8-mm zone, the RA and IA of the anterior cornea increased significantly ( P ⩽ 0.002), whereas SMILE induced an insignificant increase in RA and Asymmetry ( P ≥ 0.276) and a decrease in Irregularities ( P = 0.770). At the 8-mm zone of the posterior cornea, the Irregularities increased significantly ( P = 0.027) after FS-LASIK, whereas SMILE induced no significant changes in the examined variables ( P ≥ 0.347). RA and IA of the total cornea increased significantly after FS-LASIK ( P ⩽ 0.001), whereas SMILE induced an insignificant increase in RA and Asymmetry ( P ≥ 0.092) and a significant decrease in Irregularities ( P < 0.001). FS-LASIK induced a greater decrease in SC of the total cornea at ring 4 ( P = 0.009). Conclusions: FS-LASIK resulted in a greater increase in RA and Irregularities and greater flattening of the midperiphery of the anterior and total cornea compared with SMILE. The posterior cornea remained unaffected after SMILE, whereas more Irregularities were induced after FS-LASIK over the 8-mm zone. Abstract : Supplemental Digital Content is Available in the Text.